An ultrasonic flocculation method for composite adhesive, a rubber composite masterbatch and its preparation method
Patent Information
- Application Number
- CN202611261909.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
(1)絮凝速度极快,生产效率高:传统加酸絮凝工艺需要6 h以上的静置时间,而本申请提供的超声絮凝方法利用高功率密度超声的空化效应,可使胶乳在60 s内完成絮凝,絮凝效率提高360倍以上;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application belongs to the field of rubber wet mixing technology, and relates to an ultrasonic flocculation method for composite rubber slurry, rubber composite masterbatch and its preparation method. Background Technology
[0002] Wet mixing technology involves preparing reinforcing fillers such as carbon black and silica into an aqueous slurry, which is then mixed with natural or synthetic latex (such as styrene-butadiene latex and chloroprene latex) in a liquid state. The low viscosity of the liquid phase allows for nanoscale dispersion of the fillers within the rubber matrix. Compared to traditional dry mixing technology, this method effectively inhibits filler agglomeration, achieving uniform nanoscale dispersion of the fillers in the rubber matrix. This significantly improves the abrasion resistance and dynamic mechanical properties of the final vulcanizate, while substantially reducing mixing energy consumption. It is currently one of the key technologies for producing high-performance green tires.
[0003] With the development of tire energy conservation and emission reduction and new energy vehicles, the application of high-filler systems (especially high-precision silica filler systems) is becoming increasingly widespread. These systems use extremely high filler content, with the dry rubber to filler mass ratio reaching 100:140 or even higher. However, this dramatic increase in filler proportion poses a severe challenge to existing flocculation processes: on the one hand, high solids content leads to poor slurry stability, making sedimentation or uneven flocculation highly likely; on the other hand, the increase in filler aggregates exponentially increases the difficulty of achieving nanoscale uniform dispersion.
[0004] At present, the industrial production of wet mixing generally relies on chemical flocculation to achieve the co-precipitation of latex and filler mixtures. The main methods include the following: (1) Acid flocculation: Acid flocculation requires the use of organic acids, which has problems such as corrosion of equipment and discharge of acidic waste gas and wastewater. It also requires a large amount of clean water washing, with a water consumption of about 8 to 15 tons per ton of dry rubber. The COD of the wastewater is as high as 2000 to 5000 mg / L. Moreover, for high-filled systems, acid flocculation is even more difficult to achieve uniform flocculation. (2) Inorganic salt flocculation: Inorganic salts such as calcium chloride and sodium chloride are used as flocculants. Subsequent washing and desalination are required, making wastewater treatment difficult. Furthermore, the residual metal ions will affect the heat and oxygen aging resistance of rubber. (3) Spray drying flocculation: For example, CN105419009A discloses the use of semi-open superheated steam spray drying to prepare high-filled composite masterbatch. The filler content can reach 25 to 120% of the dry rubber mass. However, it requires specific spray drying equipment, has high energy consumption, and the spray drying process may cause rubber oxidation aging. (4) High-speed jet flocculation: For example, the high-speed jet technology developed by East China University of Science and Technology uses the huge shear force generated by the high-speed jet field to destroy the protective layer around the latex particles, so that the natural latex is demulsified and dehydrated. Although this method does not require chemical flocculants, it requires high-pressure jet equipment, and the processing capacity is limited by the size of the jet nozzle. Its adaptability to highly filled systems needs to be verified. (5) Multi-stage dispersion flocculation: For example, CN122037326A discloses a multi-stage pretreatment method that combines chemical compound modification (silane coupling agent and lignin sulfonate composite dispersant) and physical homogenization (high-pressure homogenization) to improve the degree of filler dispersion. However, this method still relies on chemical dispersants, and the process steps are relatively complex. In addition, the emulsifiers used in synthetic latex (especially styrene-butadiene latex, chloroprene latex, etc.) systems are difficult to completely remove in conventional flocculation processes. Residual emulsifiers may affect the purity, transparency and electrical properties of the product.
[0005] In summary, the existing wet mixing technology still largely relies on chemical flocculants or requires special and expensive equipment for the flocculation process, and still suffers from problems such as heavy environmental pollution, difficulty in wastewater treatment, residual additives affecting rubber properties, uneven flocculation, and high equipment requirements.
[0006] Therefore, there is an urgent need to develop an ultrasonic flocculation method for composite mortar that is completely independent of any chemical flocculants, environmentally friendly, requires simple equipment, and has high flocculation efficiency. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the purpose of this application is to provide an ultrasonic flocculation method for composite mortar, a rubber composite masterbatch and its preparation method. The ultrasonic flocculation method utilizes the ultrasonic cavitation effect to disrupt the stability of colloids in the composite mortar, enabling the composite mortar to complete flocculation. It has advantages such as high flocculation efficiency, strong versatility, simple equipment, and low water consumption and environmental friendliness. It is particularly suitable for high-filler systems and has important practical significance for energy conservation, emission reduction and high-end product development in the rubber industry.
[0008] To achieve this objective, the present application adopts the following technical solution: In a first aspect, this application provides an ultrasonic flocculation method for composite mortar, the ultrasonic flocculation method comprising: subjecting a composite mortar comprising rubber latex and filler to ultrasonic treatment under a power density of 1~8 kW / L (e.g. 1 kW / L, 2 kW / L, 3 kW / L, 4 kW / L, 5 kW / L, 6 kW / L, 7 kW / L or 8 kW / L, etc.) to complete the ultrasonic flocculation of the composite mortar.
[0009] Ultrasonic technology has been applied in water treatment, sludge dewatering, and material preparation. These applications have shown that when ultrasound propagates in liquids, it produces cavitation, which is the process of a large number of microbubbles forming, growing, and collapsing in a very short time. Accompanying the formation and collapse of microbubbles, the solution system is agitated at high speed.
[0010] Based on the above, the ultrasonic flocculation method provided in this application mainly utilizes the cavitation effect of ultrasonic technology. By controlling the power density of the ultrasound to 1~8 kW / L, the protective layer of latex particles in the composite mortar is destroyed (whether it is the protein-lipid protective layer of natural latex or the emulsifier stabilizing layer of synthetic latex). The latex particles lose stability and completely flocculate, which has the advantages of high flocculation efficiency, strong versatility, simple equipment, and low water consumption and environmental friendliness. At the same time, while achieving flocculation, the strong microjets and local high temperature and high pressure generated by the high power density ultrasound cavitation effect can effectively break the agglomerates of nanofillers, realize the nanoscale uniform dispersion of fillers in the rubber matrix, and significantly improve the dispersion uniformity of fillers. Therefore, the ultrasonic flocculation method provided in this application is also particularly suitable for high-filler systems.
[0011] Furthermore, unlike existing technologies that use low-power-density ultrasound (such as ultrasonic oscillators) which cannot effectively demulsify and disperse, the high-power-density ultrasound (power density of 1~8 kW / L) used in this application can provide sufficient cavitation energy, successfully overcoming the limitations of low-power-density ultrasound in effectively demulsifying and dispersing, and achieving rapid and uniform flocculation in a highly filled system. If the power density of the ultrasound is less than 1 kW / L, the cavitation intensity is insufficient, making it difficult to fully destroy the protective layer on the surface of latex particles, which can easily lead to incomplete flocculation, excessively long flocculation time, or small and loose flocs. If the power density of the ultrasound is greater than 8 kW / L, the cavitation intensity is too strong, which can easily cause the system temperature to rise too quickly, the rubber molecular chains to degrade, and the flocs to break down again, all of which affect the subsequent dehydration efficiency and the mechanical properties of the resulting rubber composite masterbatch.
[0012] It should also be noted that the power density of the ultrasonic treatment described in this application is based on the working volume of the ultrasonic cavity. In actual industrial implementation, a tubular continuous flow ultrasonic reactor is preferred. The required power density is achieved by using a small-volume ultrasonic cavity with a short residence time. Multiple ultrasonic units can be connected in parallel to increase the processing capacity, so as to ensure the uniformity of the sound field and engineering feasibility.
[0013] In some specific embodiments, the mass ratio of dry rubber to filler in the composite adhesive is 100:(5~150), for example, 100:5, 100:10, 100:15, 100:20, 100:30, 100:40, 100:50, 100:60, 100:70, 100:80, 100:90, 100:100, 100:120, 100:140, or 100:150. Specifically, in the high-precision silica-filled solution-polymerized styrene-butadiene rubber system, the ratio of SSBR (dry rubber):precipitated silica:carbon black is 100:(120~140):(6~10).
[0014] In some specific embodiments, the solid content of the rubber latex is 15-65%, such as 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or 65%, etc.
[0015] In some specific embodiments, the rubber latex includes natural rubber latex and / or synthetic rubber latex.
[0016] In some specific embodiments, the synthetic rubber latex includes any one or a combination of at least two of the following: styrene-butadiene latex (SBR), carboxylated styrene-butadiene latex, styrene-butadiene pyridine latex, chloroprene latex (CRL), nitrile butadiene latex (NBR), polybutadiene latex (BR), butyl latex (IIR), ethylene propylene latex (EPDM), polyisoprene latex (IR), fluororubber latex (FKM), or silicone rubber latex (VMQ).
[0017] In some specific embodiments, the filler includes any one or a combination of at least two of the following: silica, carbon black, calcium carbonate, montmorillonite, graphene oxide, carbon nanotubes, kaolin, talc, clay, or barium sulfate.
[0018] In some specific embodiments, the composite adhesive is obtained by mixing rubber latex and filler dispersion.
[0019] In some specific embodiments, the mass percentage of the filler in the filler dispersion is 10-40%, such as 10%, 15%, 20%, 25%, 30%, 35%, or 40%.
[0020] In some specific embodiments, the filler dispersion includes filler and water.
[0021] In some specific embodiments, the packing material is a silane coupling agent modified packing material.
[0022] It should be noted that the silane coupling agent modified filler is a conventional filler in the art, including but not limited to bis-[γ-(triethoxysilyl)propyl]tetrasulfide (Si-69) modified filler and bis-[γ-(triethoxysilyl)propyl]disulfide modified filler.
[0023] In some specific embodiments, the filler dispersion also includes a dispersant.
[0024] In some specific embodiments, the dispersant includes any one or a combination of at least two of lignin sulfonates, alkylbenzene sulfonates, alkyl sulfonates, alkyl sulfates, α-olefin sulfonates, sulfosuccinates, or fatty acid salts.
[0025] In some specific embodiments, the frequency of the ultrasonic treatment is 15~50 kHz, such as 15 kHz, 20 kHz, 25 kHz, 30 kHz, 35 kHz, 40 kHz, 45 kHz or 50 kHz.
[0026] In some specific embodiments, the duration of the ultrasonic treatment is 10 to 60 seconds, such as 10 seconds, 15 seconds, 20 seconds, 25 seconds, 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, or 60 seconds.
[0027] In some specific embodiments, the temperature of the ultrasonic treatment is 20~80℃, such as 20℃, 30℃, 40℃, 50℃, 60℃, 70℃ or 80℃.
[0028] In this application, the power density of the ultrasonic treatment is preferably 2~6 kW / L, more preferably 4~6 kW / L, and the treatment time is preferably 20~45 s; however, for high-filler composite mortar systems (dry adhesive:filler = 100:(120~150)), since the composite mortar has a high solid content and high viscosity, the power density can be appropriately increased to 4~8 kW / L, and the treatment time can be extended to 30~60 s to ensure sufficient cavitation effect and achieve rapid and uniform flocculation of the composite mortar.
[0029] In some specific embodiments, the ultrasonic processing mode is any one of pulse wave mode, continuous wave mode, frequency-modulated ultrasound mode, frequency-sweeping ultrasound mode, or dual-frequency ultrasound mode, and is more preferably pulse wave mode.
[0030] In some specific embodiments, the ultrasonic treatment is performed using a pulse wave mode, with a pulse wave duty cycle of 30-70%, such as 30%, 40%, 50%, 60%, or 70%, to reduce the thermal effect while having little impact on the flocculation effect.
[0031] In addition, it should be noted that, in order to further improve the flocculation effect, flocculants can be added during the ultrasonic treatment process to assist in flocculation. This application does not have any special requirements on the type of flocculant, including but not limited to acid flocculants (such as sulfuric acid, hydrochloric acid, formic acid, etc.), inorganic salt flocculants (calcium chloride, magnesium chloride, etc.) and polymeric flocculants (polyacrylamide, polydimethyldiallylammonium chloride, etc.).
[0032] Secondly, this application provides a method for preparing a rubber composite masterbatch, the method comprising: firstly flocculating the composite slurry using the ultrasonic flocculation method described in the first aspect, and then dehydrating and drying it to obtain the rubber composite masterbatch.
[0033] In some specific embodiments, the dewatering is carried out in a twin-screw extruder, belt filter press, plate and frame filter press, or vibrating dewatering screen; wherein, the distance between the screw and the cylinder wall of the screw extruder gradually changes from 10 mm to 3 mm.
[0034] In some specific embodiments, the drying temperature is 60~85℃, such as 60℃, 62℃, 64℃, 66℃, 68℃, 70℃, 72℃, 74℃, 76℃, 78℃, 80℃ or 85℃, etc.
[0035] In some specific embodiments, the drying is carried out in a mesh belt dryer, a fluidized bed dryer, a flash dryer, or a vacuum dryer.
[0036] In some specific embodiments, the moisture content of the dehydrated and dried system is <8‰.
[0037] Thirdly, this application provides a rubber composite masterbatch, which is prepared by the preparation method described in the second aspect.
[0038] Compared with the prior art, this application has the following advantages: (1) The flocculation speed is extremely fast and the production efficiency is high: the traditional acid flocculation process requires more than 6 hours of standing time, while the ultrasonic flocculation method provided in this application utilizes the cavitation effect of high power density ultrasound, which can make the latex complete flocculation within 60 seconds, and the flocculation efficiency is increased by more than 360 times. (2) Green and environmentally friendly: The ultrasonic flocculation method provided in this application uses the high power density ultrasonic cavitation effect to destroy the stability of latex, without introducing any chemical additives, and is completely free of acid and chemical flocculants; (3) Significantly reduced water consumption and recyclable wastewater: Since no chemical substances that need to be removed are introduced, the water consumption is only 5-20% of that of the traditional acid flocculation process, and the wastewater discharge reduction rate reaches 80-95%; (4) Significantly improved uniformity of filler dispersion: While achieving flocculation, the strong micro-jets and local high temperature and high pressure generated by the high power density ultrasound cavitation effect can effectively break the agglomerates of nanofillers, realize the uniform nano-level dispersion of fillers in the rubber matrix, and can handle ultra-high filler systems with a dry rubber:filler ratio of up to 100:150. (5) Extremely versatile: The ultrasonic flocculation method provided in this application is applicable to natural latex, various synthetic latexes and their mixed latexes and various filler systems such as silica and carbon black; (6) The equipment is compact and easy to industrialize and produce continuously: The ultrasonic flocculation method provided in this application can be adapted to tubular continuous flow ultrasonic reactors. The equipment occupies a small area and does not require a large area flocculation tank. It can realize full-process automated control and is easier to scale up industrially than high-speed jet technology. Detailed Implementation
[0039] The technical solution of this application will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of this application and should not be construed as specific limitations thereof.
[0040] The detailed information of some of the raw materials involved in the following specific implementation method is shown below: (1) Natural latex: The solid content is 60%, which is commercially available concentrated natural latex purchased from Hainan Natural Rubber Industry Group Co., Ltd. (2) Chloroprene latex: solid content is 50%, it is commercially available anionic chloroprene latex SNL511A, purchased from Shanna Synthetic Rubber Co., Ltd.
[0041] Preparation Example 1 A composite adhesive, the preparation method of which includes the following steps: (1) Preparation of carbon black dispersion: Take 18 kg of N330 carbon black and 82 kg of deionized water, add 0.25 kg of sodium lignosulfonate dispersant, grind and disperse in a sand mill at 2000 rpm for 20 min to prepare a carbon black dispersion with a solid content of 18%. (2) Preparation of composite adhesive: Take 41.7 kg of natural latex with a solid content of 60% (containing 25 kg of dry rubber) and mix it with 41.7 kg of carbon black dispersion obtained in step (1) (containing 7.5 kg of carbon black, dry rubber: carbon black = 100:30). Stir at 200 rpm for 5 min in a mixing tank to obtain the composite adhesive.
[0042] Preparation Example 2 A composite adhesive, the preparation method of which includes the following steps: (1) Preparation of silica dispersion: Take 25 kg of Si69 modified precipitated silica with an average particle size of 20 nm and mix it with 75 kg of deionized water. Disperse the silica in a high-speed shear disperser at 2000 rpm for 25 min to prepare silica dispersion with a solid content of 25%. (2) Preparation of composite adhesive: Take 33.3 kg of natural latex with a solid content of 60% (containing 20 kg of dry latex) and mix it with 40 kg of silica dispersion obtained in step (1) (containing 10 kg of silica, dry latex: silica = 100:50). Stir at 200 rpm for 8 min in a mixing tank to obtain the composite adhesive.
[0043] Preparation Example 3 A composite adhesive, the preparation method of which includes the following steps: (1) Preparation of silica dispersion: Take 36 kg of Si-69 modified high dispersibility silica and 64 kg of deionized water, add 1.2 kg of sodium dodecylbenzenesulfonate, disperse in a sand mill at 2500 rpm for 35 min, and then treat under heating conditions at 80℃ for 3 h to prepare silica dispersion with a solid content of 36%. (2) Preparation of composite adhesive: Take 166.67 kg of natural latex with a solid content of 60% (containing 100 kg of dry latex) and mix it with 333.3 kg of silica dispersion obtained in step (1) (containing 120 kg of silica, dry latex: silica = 100:120). Stir at 150 rpm for 15 min in a mixing tank to obtain the composite adhesive.
[0044] Preparation Example 4 A composite adhesive, the preparation method of which includes the following steps: (1) Preparation of silica dispersion: Take 40 kg of Si-69 modified high dispersibility silica and mix it with 58.6 kg of deionized water, add 1.4 kg of sodium dodecylbenzenesulfonate, disperse it in a sand mill at 2500 rpm for 40 min, and then treat it under heating conditions at 80℃ for 3 h to prepare silica dispersion with a solid content of 40%. (2) Preparation of composite adhesive: Take 166.67 kg of natural latex with a solid content of 60% (containing 100 kg of dry latex) and mix it with 350 kg of silica dispersion obtained in step (1) (containing 140 kg of silica, dry latex: silica = 100:140). Stir at 150 rpm for 15 min in a mixing tank to obtain the composite adhesive.
[0045] Preparation Example 5 A composite adhesive, the preparation method of which includes the following steps: (1) Preparation of silica dispersion: Take 39 kg of Si-69 modified high dispersibility silica and 61 kg of deionized water, add 1.4 kg of sodium dodecylbenzenesulfonate, disperse in a sand mill at 2500 rpm for 35 min, and then treat under heating conditions at 80℃ for 3 h to prepare silica dispersion with a solid content of 39%. (2) Preparation of carbon black dispersion: Take 10 kg of N234 carbon black, mix it with 40 kg of deionized water, add 0.15 kg of sodium dodecylbenzenesulfonate, and disperse it in a sand mill at 2000 rpm for 20 minutes to prepare a carbon black dispersion with a solid content of 20%. (3) Preparation of composite adhesive: Take 500 kg of chloroprene latex with a solid content of 55% (containing 275 kg of dry rubber), mix it with 333.3 kg of silica dispersion obtained in step (1) (containing 130 kg of silica) and 50 kg of carbon black dispersion obtained in step (2) (containing 10 kg of carbon black) (dry rubber: silica: carbon black = 100:47:3.6), and stir in a mixing tank at 150 rpm for 15 min to obtain the composite adhesive.
[0046] Example 1 An ultrasonic flocculation method for a composite mortar specifically includes the following steps: the composite mortar obtained in Preparation Example 1 is subjected to ultrasonic treatment in pulse wave mode, the duty cycle of the pulse wave is 30%, the frequency of ultrasonic treatment is 20 kHz, the power density is 1 kW / L, the temperature is 45℃, and the ultrasonic treatment time is 30 s, thereby completing the ultrasonic flocculation of the composite mortar.
[0047] Example 2 An ultrasonic flocculation method for a composite mortar specifically includes the following steps: the composite mortar obtained in Preparation Example 2 is subjected to ultrasonic treatment using a pulse wave mode, the duty cycle of the pulse wave is 40%, the frequency of ultrasonic treatment is 20 kHz, the power density is 1.3 kW / L, the temperature is 50℃, and the ultrasonic treatment time is 35 s, thereby completing the ultrasonic flocculation of the composite mortar.
[0048] Example 3 An ultrasonic flocculation method for a composite mortar specifically includes the following steps: the composite mortar obtained in Preparation Example 3 is subjected to ultrasonic treatment using a pulse wave mode, the duty cycle of the pulse wave is 50%, the frequency of the ultrasonic treatment is 20 kHz, the power density is 2 kW / L, the temperature is 60℃, and the ultrasonic treatment time is 50 s, thereby completing the ultrasonic flocculation of the composite mortar.
[0049] Example 4 An ultrasonic flocculation method for a composite mortar specifically includes the following steps: the composite mortar obtained in Preparation Example 4 is subjected to ultrasonic treatment using a pulse wave mode, the duty cycle of the pulse wave is 70%, the frequency of the ultrasonic treatment is 20 kHz, the power density is 3 kW / L, the temperature is 60℃, and the ultrasonic treatment time is 60 s, thereby completing the ultrasonic flocculation of the composite mortar.
[0050] Example 5 An ultrasonic flocculation method for a composite mortar specifically includes the following steps: the composite mortar obtained in Preparation Example 5 is subjected to ultrasonic treatment in pulse wave mode, the duty cycle of the pulse wave is 60%, the frequency of ultrasonic treatment is 20 kHz, the power density is 3 kW / L, the temperature is 60℃, and the ultrasonic treatment time is 60 s, thereby completing the ultrasonic flocculation of the composite mortar.
[0051] Example 6 An ultrasonic flocculation method for a composite mortar specifically includes the following steps: The composite mortar obtained in Preparation Example 4 is subjected to ultrasonic treatment using a pulse wave mode. The pulse wave duty cycle is 50%, the power density of the ultrasonic treatment is 4 kW / L, the treatment time is 35 s, the temperature is 50℃, and the frequency is 20 kHz. Example 7 An ultrasonic flocculation method for composite mortar is disclosed, which differs from Example 6 in that the ultrasonic power density is adjusted to 6 kW / L and the time is 25 s, while all other aspects are the same as in Example 6.
[0052] Example 8 An ultrasonic flocculation method for composite mortar is disclosed, which differs from Example 6 in that the ultrasonic power density is adjusted to 8 kW / L and the time is 20 s, while all other aspects are the same as in Example 6.
[0053] Example 9 An ultrasonic flocculation method for composite mortar is disclosed, which differs from Example 6 in that the ultrasonic power density is adjusted to 2 kW / L and the time is 45 s, while all other aspects are the same as in Example 6.
[0054] Example 10 An ultrasonic flocculation method for composite mortar is disclosed, which differs from Example 6 in that the ultrasonic power density is adjusted to 1 kW / L and the time is 60 s, while all other aspects are the same as in Example 6.
[0055] Example 11 An ultrasonic flocculation method for composite mortar is disclosed, which differs from Example 6 in that the temperature is 20°C, while all other aspects are the same as in Example 6.
[0056] Example 12 An ultrasonic flocculation method for composite mortar is disclosed, which differs from Example 6 in that the ultrasonic treatment temperature is adjusted to 90°C, while all other aspects are the same as in Example 6.
[0057] Comparative Example 1 A flocculation method for a composite adhesive specifically includes the following steps: adding acetic acid to the composite adhesive obtained in Preparation Example 1 to adjust the pH of the system to 4.5, letting it stand for 7 h, washing it 3 times to complete the flocculation of the composite adhesive, using approximately 15 tons of water per ton of dry adhesive, and the COD of the wastewater is approximately 3500 mg / L.
[0058] Comparative Example 2 A flocculation method for a composite adhesive includes the following steps: adding calcium chloride (3% of the dry adhesive mass) and sulfuric acid (to adjust the pH to 5.0) to the composite adhesive obtained in Preparation Example 4, stirring for 15 min to complete flocculation, and then washing with clean water three times to remove residual salts, thereby completing the flocculation of the composite adhesive.
[0059] Comparative Example 3 A flocculation method for a composite mortar specifically includes the following steps: the composite mortar obtained in Preparation Example 4 is treated with a common ultrasonic oscillator (power of 100 W, frequency of 40 kHz, power density of about 5 W / L) for 10 min, and the composite mortar still does not form flocculent clumps that can be mechanically dehydrated.
[0060] Comparative Example 4 A flocculation method for a composite mortar specifically includes the following steps: the composite mortar obtained in Preparation Example 4 is processed by a high-speed jet device (nozzle diameter of 1 mm, jet velocity of 100 m / s) to complete the flocculation of the composite mortar.
[0061] Comparative Example 5 A flocculation method for composite mortar, which differs from Example 6 in that the ultrasonic power density is adjusted to 0.5 kW / L and the time is 100 s, while all other aspects are the same as in Example 6.
[0062] Comparative Example 6 A flocculation method for composite mortar, which differs from Example 6 in that the ultrasonic power density is adjusted to 10 kW / L and the time is 100 s, while all other aspects are the same as in Example 6.
[0063] Performance testing: The flocculent masterbatch particles obtained after flocculation in Examples 1-12 and Comparative Examples 1-6 were dehydrated and dried until the moisture content was less than 8‰ to obtain rubber composite masterbatch. Then, natural vulcanizates and chloroprene vulcanizates were prepared according to the following method: Natural vulcanized rubber: Based on 100 parts by weight of dry rubber, add 3 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1.5 parts by weight of antioxidant 4020, 1.5 parts by weight of accelerator CBS, 1.0 part by weight of accelerator DPG and 1.5 parts by weight of sulfur; first, mix all components except accelerator and sulfur in an internal mixer, then add accelerator and sulfur on a two-roll mill and mix evenly to obtain vulcanized rubber, and then perform the following tests on the obtained vulcanized rubber; Chloroprene vulcanizate: Based on 100 parts by weight of dry rubber, add 5 parts by weight of zinc oxide, 4 parts by weight of magnesium oxide, 0.5 parts by weight of stearic acid, 1.5 parts by weight of antioxidant 4020, 1.5 parts by weight of antioxidant RD, and 0.5 parts by weight of sulfur; after all components are mixed in an internal mixer and mixed evenly, vulcanizate is obtained, and then the obtained vulcanizate is tested as follows; (1) Tensile strength, elongation at break and stress at 300% constant elongation: Tested according to the methods provided in GB / T 528-2009; (2) Shore A hardness: The test was conducted using a Shore A hardness tester, referring to the method provided in GB / T 531.1-2008; (3) Packing dispersion grade: Refer to the sample preparation and image evaluation method specified in GB / T 6030-2006; (4) Dynamic mechanical properties: tested using a dynamic thermomechanical analyzer; (5) Abrasion resistance: Tested according to the Akron abrasion test method provided in GB / T 1689-2014.
[0064] Table 1 According to the data in Table 1: The flocculation methods provided in Examples 1-12 can all enable the composite adhesive to form dehydrated and dry flocculent masterbatch particles; and can ensure that the tensile strength of the final vulcanized rubber is not less than 21.4 MPa, the elongation at break is not less than 360%, the stress at 300% constant elongation is not less than 9.6 MPa, the filler dispersion grade is not less than 7.5, the tanδ at 60℃ is not more than 0.075, the tanδ at 0℃ is not less than 0.32, and the Akron abrasion is not more than 0.25 cm. 3 / 1.61km indicates that the flocculation method provided in this application can maintain good packing dispersibility, mechanical properties, dynamic mechanical properties and wear resistance while achieving rapid flocculation.
[0065] Compared with the examples, the flocculation method provided in Comparative Example 1 uses acetic acid flocculation, which not only has a long processing time, large water consumption, and high COD of wastewater, but also results in low filler dispersibility and overall performance of the vulcanized rubber. The flocculation method provided in Comparative Example 2 uses calcium chloride and sulfuric acid for chemical flocculation, which easily leads to uneven flocculation in a high-filler system, resulting in a significant decrease in the tensile strength and abrasion resistance of the vulcanized rubber. The flocculation method provided in Comparative Example 3 uses ordinary low-power ultrasound, which cannot form mechanically dehydrated flocs. The flocculation method provided in Comparative Example 4 uses high-speed jet treatment, which has problems such as easy nozzle clogging, limited processing capacity, and uneven shearing. The flocculation method provided in Comparative Example 5 has a power density of only 0.5 kW / L, and even with extended processing time, it still suffers from insufficient flocculation, a large amount of free filler, and a decrease in vulcanized rubber performance. The flocculation method provided in Comparative Example 6 has an excessively high power density, which causes the formed flocs to undergo secondary breakage under strong cavitation microjet and shearing action, and causes mechanical damage to some rubber molecular chains.
[0066] Furthermore, as can be seen from Examples 1-5, the flocculation method provided in this application is applicable to natural latex, chloroprene latex, and carbon black, silica, and composite filler systems. Even under high-filling conditions where the dry rubber to silica mass ratio reaches 100:120 and 100:140, the filler dispersion grade of the obtained vulcanized rubber can still reach 8.5 or higher, indicating that this application has good adaptability to high solids content, high viscosity, and high-filling composite adhesives.
[0067] Further, as can be seen from Examples 6-10, under the same conditions, increasing the power density from 1 kW / L to 2 kW / L, 4 kW / L, and 6 kW / L respectively shortened the processing time required to complete flocculation from 60 s to 45 s, 35 s, and 25 s, respectively; improved the packing dispersion grade from 7.5 to 9.0; increased the tensile strength from 21.8 MPa to 25.4 MPa; and reduced the Akron abrasion volume from 0.25 cm³. 3 / 1.61 km decreased to 0.19 cm 3 / 1.61 km indicates that increasing the power density can enhance cavitation and improve the flocculation uniformity and filler dispersion of the high-filler composite mortar.
[0068] Further comparison of Examples 7 and 8 shows that some properties of the vulcanized rubber prepared by the flocculation method provided in Example 8 are slightly reduced. This indicates that when the power density reaches 8 kW / L, the processing time should be appropriately shortened and the temperature rise of the system should be controlled to avoid excessive cavitation causing breakage of the formed flocs. Considering the flocculation rate, filler dispersibility, material properties and energy consumption, the ultrasonic power density is preferably 2~6 kW / L. For high viscosity or ultra-high filler systems, 6~8 kW / L can be used and the processing time should be shortened.
[0069] Finally, a comparison of Examples 6, 11, and 12 shows that when the temperature is too low, the viscosity of the composite adhesive is high, which is not conducive to cavitation; when the temperature is too high, it may weaken the collapse strength of cavitation bubbles and increase the risk of heat and mechanical damage to the rubber molecular chains. Therefore, the ultrasonic treatment temperature is preferably 20~80℃, and more preferably 45~60℃.
[0070] In summary, controlling the ultrasonic power density between 1 and 8 kW / L is beneficial for achieving rapid and uniform flocculation of the composite slurry and ensuring the comprehensive performance of the resulting rubber composite masterbatch.
[0071] The above description is only a specific embodiment of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application fall within the protection and disclosure scope of this application.
Claims
1. A method for ultrasonic flocculation of a composite adhesive, characterized in that, The ultrasonic flocculation method includes: subjecting a composite slurry comprising rubber latex and filler to ultrasonic treatment under a power density of 1~8 kW / L to complete the ultrasonic flocculation of the composite slurry.
2. The ultrasonic flocculation method according to claim 1, characterized in that, The mass ratio of dry rubber to filler in the composite adhesive is 100:(5~150); And / or, the solid content of the rubber latex is 15-65%; And / or, the rubber latex includes natural rubber latex and / or synthetic rubber latex; And / or, the filler comprises any one or a combination of at least two of the following: silica, carbon black, calcium carbonate, montmorillonite, graphene oxide, carbon nanotubes, kaolin, talc, clay, or barium sulfate.
3. The ultrasonic flocculation method according to claim 2, characterized in that, The synthetic rubber latex includes any one or a combination of at least two of the following: styrene-butadiene latex, carboxylated styrene-butadiene latex, styrene-butadiene pyridine latex, chloroprene latex, nitrile latex, polybutadiene latex, butyl latex, ethylene-propylene latex, polyisoprene latex, fluororubber latex, or silicone rubber latex.
4. The ultrasonic flocculation method according to any one of claims 1 to 3, characterized in that, The composite adhesive is obtained by mixing rubber latex and filler dispersion. Preferably, the filler content in the filler dispersion is 10-40% by mass; Preferably, the filler dispersion comprises filler and water; Preferably, the filler dispersion further includes a dispersant.
5. The ultrasonic flocculation method according to claim 4, characterized in that, The filler is a silane coupling agent modified filler; And / or, the dispersant comprises any one or a combination of at least two of lignin sulfonates, alkylbenzene sulfonates, alkyl sulfonates, alkyl sulfates, α-olefin sulfonates, sulfosuccinates, or fatty acid salts.
6. The ultrasonic flocculation method according to any one of claims 1 to 5, characterized in that, The frequency of the ultrasonic treatment is 15~50 kHz; And / or, the duration of the ultrasonic treatment is 10-60 s; And / or, the temperature of the ultrasonic treatment is 20~80℃.
7. The ultrasonic flocculation method according to any one of claims 1 to 6, characterized in that, The ultrasonic processing mode is any one of pulse wave mode, continuous wave mode, frequency-modulated ultrasound, frequency-sweeping ultrasound, or dual-frequency ultrasound mode, preferably pulse wave mode. Preferably, the duty cycle of the pulse wave in the pulse wave mode is 30-70%.
8. A method for preparing a rubber composite masterbatch, characterized in that, The preparation method includes: first, flocculating the composite slurry using the ultrasonic flocculation method as described in any one of claims 1 to 7, and then dehydrating and drying it to obtain the rubber composite masterbatch.
9. The preparation method according to claim 8, characterized in that, The drying temperature is 60~85℃.
10. A rubber composite masterbatch, characterized in that, The rubber composite masterbatch is prepared using the preparation method described in claim 8 or 9.
Citation Information
Patent Citations
Method for preparing high-filling composite masterbatch through semi-open type superheated steam spray-drying method
CN105419009A
Wet-process masterbatch preparation method and system based on multistage dispersion and intelligent feedback
CN122037326A